Conservation And Management Strategies For Threatened Plant Species Of Kachchh Desert Island, Gujarat, India - Joshi, Pankaj N; Soni, Hiren B; Sunderraj, SF Wesley; Joshua, Justus (International Journal of Environment, 2013)
Climatic variations and geo-morphological conditions of a particular geographic province determine the formation of different plant communities, and thereby form the different types of habitats. One of the indispensable prerequisites for conservation of a particular species is to understand different ecological parameters determine its population status and distribution pattern. The present study focuses on the status and distribution of threatened and medicinal plant species in various types of habitats and ecosystems of Kachchh Desert Island, Gujarat, India. Besides opportunistic observations of floral elements, conservation and management of some medicinal and threatened plant species is discussed. The study also depicts the understanding of role of environmental, ecological, economical, social and ethological factors which help to enhance the productive potential of a particular plant species alongwith its associated communities involving local people, tribal communities and local NGOs. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 45-59 DOI: http://dx.doi.org/10.3126/ije.v2i1.9207